2021
DOI: 10.1186/s12879-021-06528-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the sensitivity and specificity of lateral flow devices in the detection of SARS-CoV-2

Abstract: Background Lateral flow devices (LFDs) are viral antigen tests for the detection of SARS-CoV-2 that produce a rapid result, are inexpensive and easy to operate. They have been advocated for use by the World Health Organisation to help control outbreaks and break the chain of transmission of COVID-19 infections. There are now several studies assessing their accuracy but as yet no systematic review. Our aims were to assess the sensitivity and specificity of LFDs in a systematic review and summari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 32 publications
8
87
3
4
Order By: Relevance
“…The authors conclude that LFD specificity ranged from 92.4% to 100%. In particular, the manufacturer Bioeasy was highlighted as the only LFD supplier with an average specificity <97% [49]. These results are in agreement with the study conducted by the UK COVID-19 Lateral Flow Oversight Team which was designed to analyse the efficacy of LFDs suppliers to the UK [50].…”
Section: A Computational Framework For Estimating Transmission With Npissupporting
confidence: 86%
See 2 more Smart Citations
“…The authors conclude that LFD specificity ranged from 92.4% to 100%. In particular, the manufacturer Bioeasy was highlighted as the only LFD supplier with an average specificity <97% [49]. These results are in agreement with the study conducted by the UK COVID-19 Lateral Flow Oversight Team which was designed to analyse the efficacy of LFDs suppliers to the UK [50].…”
Section: A Computational Framework For Estimating Transmission With Npissupporting
confidence: 86%
“…Furthermore, the systematic review of LFD efficacy conducted by Mistry et al [49] found that LFD sensitivities ranged from 37.7% to 99.2%, highlighting that LFD falsenegative rates are not only dependent on the manufacturer but also on the operator, and thus we consider the probability of LFD false-negative result to be variable.…”
Section: A Computational Framework For Estimating Transmission With Npismentioning
confidence: 97%
See 1 more Smart Citation
“…Though Lateral Flow Device (LFD) testing data are available within SAIL for linkage studies, we chose not to use LFD data. Meta-analysis of LFD testing has found that it has poor sensitivity in detecting SARS-CoV-2 infection [ 19 ], and potentially provides high false positive rates when community cases rates are low [ 20 ]. Furthermore, as SARS-CoV-2 testing policy in Wales is that a positive lateral flow test be followed by a confirmatory PCR test, then people with SARS-CoV-2 identified through positive LFD tests would, in most cases, be recorded under the more reliable PCR testing process [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of our results is dependent on the quality of data collected. Numerous factors influence the diagnostic sensitivity of RA tests relative to RT-PCR, such as the level of training of those who collect the samples, anatomical collection site, and storage conditions [72][73][74][75] . Substantial heterogeneity across RA tests exists in the assessment period of their sensitivity.…”
Section: Discussionmentioning
confidence: 99%